A practical guide to optimizing the benefits of post-stroke spasticity interventions with botulinum toxin A: An international group consensus - Gerard E. Francisco; Alexander Balbert; Ganesh Bavikatte; Djamel Bensmail; Stefano Carda; Thierry Deltombe; Nathalie Draulans; Steven Escaldi; Raphael Gross; Jorge Jacinto; Nicholas Ketchum; Franco Molteni; et al. (Medical Journals Sweden, 2021)
This consensus paper is derived from a meeting of an international group of 19 neurological rehabilitation specialists with a combined experience of more than 250 years (range 4-25 years; mean 14.1 years) in treating post-stroke spasticity with botulinum toxin A. The group undertook critical assessments of some recurring practical challenges, not yet addressed in guidelines, through an exten-sive literature search. They then discussed the results in the light of their individual clinical experience and developed consensus statements to present to the wider community who treat such patients. The analysis provides a comprehensive overview of treatment with botulinum toxin A, including the use of adjunctive therapies, within a multidisciplinary context, and is aimed at practicing clinicians who treat patients with post-stroke spasticity and require further practical guidance on the use of botulinum toxin A. This paper does not replicate information published elsewhere, but instead aims to provide practical advice to help optimize the use of botulinum toxin A and maximize clinical outcomes. The recommendations for each topic are summarized in a series of statements. Where published high-quality evidence exists, the recommendations reflect this. However, where evidence is not yet conclusive, the group members issued statements and, in some cas-es, made recommendations based on their clinical experience.